Structural diversity and functional variability of gut microbial communities associated with honey bees. (January 2020) - Khan, Khalid Ali; Al-Ghamdi, Ahmad A.; Ghramh, Hamed A.; Ansari, Mohammad Javed; Ali, Habib; Alamri, Saad A.; Al- Kahtani, Saad Naser; Adgaba, Nuru; Qasim, Muhammad; Hafeez, Muhammad
Abstract: Microbial consortia accompanied to all eukaryotes can be inherited from ancestors, environment, and/or from various food source. Gut microbiota study is an emerging discipline of biological sciences that expands our understanding of the ecological and functional dynamics of gut environments. Microorganisms associated with honey bees play an important role in food digestion, colony performance, immunity, pollination, antagonistic effect against different pathogens, amelioration of food and many more. Although, many repots about honey bee gut microbiota are well documented, microbiome with other key components of honey bees such as larvae, adults, their food (pollen, beebread, and honey), honey combs, and floral nectar are poorly understood. Mutual interactions and extent of the roles of microbial communities associated with honey bees are still unclear and demand for more research on the nutritional physiology and health benefits of this ecologically and economically important group. Here in this study, we highlighted all the honey bee microbiome that harbored from different life stages and other relevant components. The anatomical parts of honey bee (larvae, adults), food source (pollen, beebread, and honey), honey combs, and floral nectar were highly flourished by numerous microorganisms like bacteria (Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, Actinobacteria, Actinomycetes, Bacilli, Bacteroidetes, Cocci, Clostridia, Coliforms, Firmicutes, Flavobacteriia, Mollicutes) and fungi (Dothideomycetes, Eurotiomycetes, Mucormycotina, Saccharomycetes, Zygomycetes, Yeasts, Molds). Some distinctive microbial communities of a taxonomically constrained species have coevolved with social bees. This contribution is to enhance the understanding of honey bee gut microbiota, to accelerate bee microbiota and microbiome research in general and to aid design of future experiments in this growing field. Highlights: Microbial consortia accompanied to all eukaryotes can be inherited from ancestors. Gut microbiota studies is an emerging discipline that expands our understanding of the ecological and functional dynamics of gut environments. Honey bee life stage, food source, pollen comb and pollen nectar were harbored with diverse microbial communities. This study enhance the understanding of honey bee gut microbiota, to accelerate bee microbiota and microbiome research in general and to aid design of future experiments in this growing field.